Regional security in South Asia : the ethno-sectarian dimensions - Jetly, Nancy (New Delhi : Lancers Books ; Dhaka : University press, 2000)
Contributed articles presented at an international seminar in 1996.
Includes bibliographical references and index.
Keywords: National security -- South Asia; South Asia -- Politics and government; South Asia -- Ethnic relations